Ginger, from the dining table straight to the pharmacy - Jurášek, Michal; Drašar, Pavel (Chemické listy, 2022)
Common food and spice, ginger contains a plethora of biologically active compounds that may serve as a basis for pharmaceutical exploitation.
Keywords: léčivé rostliny; lidé; Plants, Medicinal; Zingiber officinale; fytoterapie; zázvor lékařský; Phytotherapy; Humans